Functionalization of polyethersulfone membrane with graphene oxide to improve membrane performance and properties for water treatment - Ntone, Ellora Priscille Ndia; Sunarti, Abd Rahman; Rozaimi, Abu Samah; Mohamad Syafiq, Abdul Wahab (AIP Publishing, 2025)
mprovement of physicochemical properties, morphological structure, permeate flux and selectivity is of great importance for membranes in water treatment, desalination and water treatment. The implementation of nanoparticles in membrane functionalization has shown positive results in the synthesis of effective performance membranes. In the recent work, graphene oxide (GO) at a concentration ranging from 0 - 0.4 wt. % was added into the top polyamide (PA) layer of polyethersulfone (PES) membrane by interfacial polymerization (IP) method. The outcome of GO on the morphology, physicochemical structure, and charge of the outermost surface layer of the membrane were examined using scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), contact angle (CA), and surface zeta potential. Permeation flux, paracetamol rejection, and fouling performance were also evaluated. Compared to the non-modified membranes, the GO modified membranes performed better. From the results, the introduction of GO reduced the CA of the membrane, which ultimately improved the hydrophilic characteristics of the membrane. The membrane with GO 0.2 wt. % had the highest permeate flux of 22.6 L/m2h and 97.7% paracetamol rejection, with a flux recovery ratio of 91.67%. These performances were better than those of the unmodified membrane. Based on these results, functionalization of membranes with GO improves the structure and performances of the membrane and provides a potential means for developing effective, durable, and resistant membranes.